2021
DOI: 10.1002/lol2.10216
|View full text |Cite
|
Sign up to set email alerts
|

Diverse arsenic‐containing lipids in the surface ocean

Abstract: Marine microbes experience constant exposure to the potentially toxic element arsenic. However, there are no baseline measurements of how much arsenic accumulates in microbial communities nor do we know the full spectrum of arsenic containing biomolecules produced in marine systems. In culture-based studies there is strong evidence that phytoplankton synthesize arsenic-containing lipids, but these lipids are only beginning to be explored within natural marine microbial communities. Here, we make measurements o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…AsLs are neutral lipid analogs (Dembitsky & Levitsky, 2004) that are abundant in marine organisms (Al Amin et al, 2018, 2020; Amayo et al, 2013, 2014; Heal et al, 2022; Liu et al, 2022; Petursdottir et al, 2016; Taylor & Karagas, 2022; Tibon et al, 2022). AsL speciations primarily include arsenic‐containing hydrocarbons (AsHCs) (Arroyo‐Abad et al, 2010), arsenic‐containing fatty acids (Sele et al, 2014), and arsenic‐containing phospholipids (AsPLs) (Chen et al, 2023; Raab et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…AsLs are neutral lipid analogs (Dembitsky & Levitsky, 2004) that are abundant in marine organisms (Al Amin et al, 2018, 2020; Amayo et al, 2013, 2014; Heal et al, 2022; Liu et al, 2022; Petursdottir et al, 2016; Taylor & Karagas, 2022; Tibon et al, 2022). AsL speciations primarily include arsenic‐containing hydrocarbons (AsHCs) (Arroyo‐Abad et al, 2010), arsenic‐containing fatty acids (Sele et al, 2014), and arsenic‐containing phospholipids (AsPLs) (Chen et al, 2023; Raab et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Biogeochemical fluxes, and in some instances, their impacts on organismal physiology, was another theme of the selected studies. Heal et al (2022) shed new light on how marine microbial communities interact with and accumulate arsenic, a potentially toxic element. They showed that in the open ocean surface waters, much of the bulk particulate arsenic is actually contained in complex lipids, some of which appear to be of bacterial origin.…”
mentioning
confidence: 99%